Religion on the Edge: De-centering and re-centering the sociology of religion - Bender, Courtney; Cadge, Wendy; Levitt, Peggy; David Smilde (Oxford Oxford University Press, 2013)
The thirteen essays in this volume offer a challenge to conventional scholarly approaches to the sociology of religion. They urge readers to look beyond congregational settings, beyond the United States, and to religions other than Christianity, and encourage critical engagement with religion's complex social consequences. By expanding conceptual categories, the essays reveal how aspects of the religious have always been part of allegedly non-religious spaces and show how, by attending to these intellectual blindspots, we can understand aspects of identity, modernity, and institutional life that have long been obscured. Religion on the Edge addresses a number of critical questions: What is revealed about the self, pluralism, or modernity when we look outside the U.S. or outside Christian settings? What do we learn about how and where the religious is actually at work and what its role is when we unpack the assumptions about it embedded in the categories we use?
Keywords: Religious sociology; Arts & Humanities; Social Sciences